N-type Ge/SiGe Multi Quantum-Wells for a THz Quantum Cascade Laser. (22nd October 2019) - Ciano, Chiara; Di Gaspare, Luciana; Montanari, Michele; Persichetti, Luca; Baldassarre, Leonetta; Ortolani, Michele; Capellini, Giovanni; Skibitzki, Oliver; Zöllner, Marvin; Faist, Jerome; Scalari, Giacomo; Stark, David; et al.
Abstract : Exploiting intersubband transitions in Ge/SiGe quantum cascade devices provides a way to integrate terahertz light emitters into silicon-based technology. With the view to realizing a Ge/SiGe Quantum Cascade Laser, we present the optical and structural properties of n-type strain-symmetrized Ge/SiGe asymmetric coupled quantum wells grown on Si(001) substrates by means of ultrahigh vacuum chemical vapor deposition. We demonstrate the high material quality of strain-symmetrized structures and heterointerfaces as well as control over the inter-well coupling and electron tunneling. Motivated by the promising results obtained on ACQWs, which are the basic building block of a cascade structure, we investigate, both experimentally and theoretically, a Ge/SiGe THz QCL design, optimized through a non-equilibrium Green's function formalism.